Evaluation of the expediency of technology commercialization: a case of information technology and biotechnology - Zemlickienė, Vaida; Turskis, Zenonas (Technological and Economic Development of Economy, 2020)
The ability to timely and objectively evaluate the expediency of technology commercialising is a crucial step for R&D organisations. It is a game with business success, which could enable to operate technologies efficiently and prevent unproductive investments. Managers in power, involved in the technology commercialization cycle, create rules for the game and are the leading players. The research establishes specifics of different technological fields, which are essential for assessing the expediency of technology commercialization. The scientific literature of technology commercialization didn’t take into account the specifics of different technological fields. The study presents the first two phases of the expediency of commercialization of the information technologies and biotechnologies evaluation models: the development of elements collections and the establishment of the importance of elements. The proposed technique could be expanded to select the most suitable technology for sustainable management of commercialization and the rational use of resources. The results of the expert’s survey aimed at establishing the importance of the elements are compared, efforts are made to identify differences in the evaluation the expediency of technology commercialization for information technologies and biotechnologies. The MCDM method has applied the selection of which was established by the motive related to the goal of evaluation – to evaluate the expediency of technology commercialization for information technologies and biotechnologies.